Digitalisasi Manajemen Aset Melalui Aplikasi Berbasis Website Dengan Metode Waterfall - Ika Rizki Noviani; Latipah Rifani; Lukman Junaedi; Natalia Damastuti (Institut Teknologi Adhi Tama Surabaya, 2026)
Manual administration of information technology assets, or management conducted through disconnected systems, frequently gives rise to complications in data recording, asset condition monitoring, and report generation. This study was conducted to design and develop a web-based application capable of supporting integrated and well-structured asset management. The development approach adopted encompasses several key stages, including requirements analysis, system design, implementation, and functional testing. The application was built utilizing PHP programming laguage under the Laravel framework, with MySQL serving as the underlying database engine. A testing phase was carried out to verify that each feature operates in accordance with the established requirements. The findings demonstrate that the developed application effectively supports asset data administration, borrowing and return transaction processing, as well as report generation. Furthermore, the resulting system contributes to improved user accessibility and greater administrative orderliness